Distant islands : the Japanese American community in New York City, 1876-1930s - Inouye, Daniel H. (George and Sakaye Aratani Nikkei in the Americas series., 2018)
"The turn of the century New York Japanese American community was a composite of several micro communities divided along status, class, geographic, and religious lines. Using primary sources Inouye tells the stories of the professional elites, small business owners, working-class, laborers, and students from these communities"--Provided by publisher.